The Y chromosome as a regulatory element shaping immune cell transcriptomes and susceptibility to autoimmune disease - Case, Laure K. (Cold Spring Harbor Laboratory Press, 2013)
Understanding the DNA elements that constitute and control the regulatory genome is critical for the appropriate therapeutic management of complex diseases. Here, using chromosome Y (ChrY) consomic mouse strains on the C57BL/6J (B6) background, we show that susceptibility to two diverse animal models of autoimmune disease, experimental allergic encephalomyelitis (EAE) and experimental myocarditis, correlates with the natural variation in copy number of Sly and Rbmy multicopy ChrY genes. On the B6 background, ChrY possesses gene regulatory properties that impact genome-wide gene expression in pathogenic CD4(+) T cells. Using a ChrY consomic strain on the SJL background, we discovered a preference for ChrY-mediated gene regulation in macrophages, the immune cell subset underlying the EAE sexual dimorphism in SJL mice, rather than CD4(+) T cells. Importantly, in both genetic backgrounds, an inverse correlation exists between the number of Sly and Rbmy ChrY gene copies and the number of significantly up-regulated genes in immune cells, thereby supporting a link between copy number variation of Sly and Rbmy with the ChrY genetic element exerting regulatory properties. Additionally, we show that ChrY polymorphism can determine the sexual dimorphism in EAE and myocarditis. In humans, an analysis of the CD4(+) T cell transcriptome from male multiple sclerosis patients versus healthy controls provides further evidence for an evolutionarily conserved mechanism of gene regulation by ChrY. Thus, as in Drosophila, these data establish the mammalian ChrY as a member of the regulatory genome due to its ability to epigenetically regulate genome-wide gene expression in immune cells.